Relationship of Vitamin A and Thyroid Function in Individuals With Obesity and After Laparoscopic Sleeve Gastrectomy - Ma, Bingwei; Yang, Peng; Gao, Jingyang; Du, Lei; Sheng, Chunjun; Usman, Taofeek; Wang, Xingchun; Qu, Shen (Frontiers in Nutrition, 2022)
Vitamin A deficiency (VAD) occurs in obesity and may be associated with thyroid dysfunction. We aimed to investigate the association of VA with thyroid function in obesity and after laparoscopic sleeve gastrectomy (LSG). 976 obese subjects were enrolled for this study and were divided into VAD, marginal vitamin A deficiency (MVAD), and vitamin A normal (NVA) groups. VAD was defined as VA≤200ng/ml, MVAD was defined as VA>200 but <300ng/ml, and NVA was defined as VA≥300 ng/ml. Thyroid function was compared among groups and the relationship of VA and thyroid function was analyzed. 244 of the 976 obese subjects underwent LSG, and the change in thyroid function and VA at 3, 6, and 12 months after surgery was measured. Results showed that 37% of all the subjects had subclinical hypothyroidism (SH), and the SH group had lower VA levels than the non-SH group(P=0.008). 49% of all the subjects had MVAD, 9% had VAD, while the MVAD or VAD group had lower FT4 than the NVA group (P=0.005 and P=0.001). The VAD group also had higher TSH than NVA group (P=0.037). VA was significantly negatively associated with TSH (r=-0.151, P=0.006) and positively associated with FT4(r=0.228, P<0.001). TSH was significantly decreased at 3,6 and 12 months (3M: from 4.43±2.70 to 2.63±1.46 mU/l, P<0.001; 6M: from 4.43±2.70 to 3.84±2.34 mU/l, P=0.041; 12M: from 4.43±2.70 to 2.85±1.68 mU/l, P=0.024). After LSG surgery, VA levels were slightly increased, when compared to pre-surgery levels, at 3, 6 and 12 months (3M:from 262.57±68.19 to 410.33±76.55 ng/ml, P=0.065; 6M:from 262.57±68.19 to 281.36±93.23 ng/ml, P=0.343; 12M: from 262.57±68.19 to 300.37±86.03ng/ml, P=0.083). SH group also had lower TSH and higher VA than the non-SH group at 3 months post-surgery (TSH: -1.4(-2.3, -0.3) vs.-0.2(-0.8, -0.2) mU/l, P<0.001; VA: 163.99±32.58 vs. 121.69±27.59 ng/ml, P=0.044). In conclusion VA, which is related to thyroid hormone production, protects against thyroid dysfunction in obese subjects. The improvement of thyroid function in subjects with SH after LSG may be related to the increased VA levels observed post-surgery.